Critiquing the presence of outsiders, women of questionable pasts in Jesus’ genealogy: lessons for contemporary Christianity (2024)
The book of Mathew has an unusual beginning and a casual reading shows a monotonous account of people “begoting” another and this itself, is somewhat boring and repetitive. Asides this repetitiveness, a striking feature of this account is the mention of four women and a fifth, Tamar, Rahab, Ruth, Bathsheba and Mary. Extant literature on the genealogy of Jesus in Matthew have largely focused on it from the perspective of his role as the messiah, his ancestry and lineage, and in comparison with the Lukan genealogy, with scant attention paid to the presence of women, especially from a critical point of view. This study, therefore critiqued the unusual mention of women in a chronicle of men given the patriarchal setting of the history. The aim of this research was to answer the following research questions: who are these women and why were they mentioned in an historical account that was predominantly masculine? What purpose did they serve in the Mathean genealogy? These questions were answered critically with the view of drawing lessons for contemporary Christians, especially as they concern women. The study used philosophical methods of contextualism and the verification principle. The study revealed that the inclusion of Tamar, Rahab, Ruth, Bathsheba and Mary in the genealogy of Christ was not accidental but purposeful, especially in a history that looked down on women. More so, many lessons could be drawn from the lives of these women by contemporary women, Christians generally and the society at large and the major one is that no one should be written off.